Fe(III) complex of biuret-amide based macrocyclic ligand as peroxidase enzyme mimic - Panda, Chakadola; Ghosh, Munmun; Panda, Tamas; Banerjee, Rahul; Sen Gupta, Sayam (Chemical Communications, 2011)
An Fe(III) complex of a biuret-amide based macrocyclic ligand that exhibits both excellent reactivity for the activation of H(2)O(2) and high stability, especially at low pH and high ionic strength, is reported.

Fine-tuning the balance between crystallization and gelation and enhancement of CO2 uptake on functionalized calcium based MOFs and metallogels - Mallick, Arijit; Schoen, Eva-Maria; Panda, Tamas; Sreenivas, K.; Diaz, David Diaz; Banerjee, Rahul (Journal of Materials Chemistry, 2012)
The synthesis, structure, gas adsorption and catalytic properties of a new 3D porous, crystalline metal-organic framework (Ca-5TIA-MOF) as well as stable viscoelastic metallogels (Ca-5TIA-Gel) are reported. Remarkably, the preparation of both types of materials can be carried out starting from the same organic ligand (i.e. 5-(1,2,4-triazoleyl) isophthalic acid (5TIA)), divalent metal ion (i.e. Ca(II)) and organic solvent (i.e. DMF). In this particular case, the presence of water in the solvent system favors the formation of a crystalline MOF, whereas a pure organic solvent induces gelation. The characterization of the materials was carried out using a series of techniques including XRD, FT-IR, TGA, TEM, SEM, SAXS and dynamic rheology. Experimental PXRD peaks of both Ca-5TIA-xerogel and Ca-5TIA-MOF matched reasonably well with simulated PXRD, suggesting the presence of, at least, some common structural elements in the 3D networks of both xerogel and crystalline phases. Moreover, the nature of the metal counteranion was found to have a critical influence on the gelation phenomenon. To the best of our knowledge, this report describes unprecedented Ca-based LMW-metallogels, as well as the first porous Ca-based MOF, which shows adsorption capacity for CO2 at 1 atm pressure. Interestingly, Ca-5TIA-xerogel presented 20% higher CO2-uptake than the crystalline Ca-5TIA-MOF at 1 atm and 298 K. Both Ca-5TIA-MOF and Ca-5TIA-Gel also displayed a modest catalytic activity towards the hydrosilylation of benzaldehyde, with slightly better performance for the gel phase material.